Board Features and Corporate Performance: A Panel Data Analysis of Moroccan Listed Firms - Tahiri, Amal; El Arif, Fatima Zahra (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).16, 2026)
Despite growing interest in corporate governance research, empirical evidence from North African emerging markets remains scarce, and no prior study has applied dynamic panel methods to assess board effectiveness in the Moroccan context using post-2018 data. This study addresses that gap by examining how board characteristics - including size, independence, gender diversity, CEO duality, foreign directors, board committees, and ownership structure - affect the performance of Moroccan listed firms. Panel data from 44 firms over 2018–2023 are analyzed using Random Effects and System GMM estimators. Tobin’s Q and Return on Assets (ROA) serve as measures of firm performance. Diagnostic tests, including Hansen and Arellano-Bond tests, confirm the robustness of the GMM models. Board independence, gender diversity, and dispersed ownership are positively associated with performance, while leverage exerts a negative influence. Board size, CEO duality, foreign directors, and committees show no significant impact. This paper makes three original contributions. First, it provides one of the first dynamic panel analyses of governance-performance linkages in Morocco using System GMM, directly addressing the endogeneity challenge that plagues cross-sectional governance studies. Second, it extends the comparative corporate governance literature to an under-studied North African market with institutional characteristics distinct from both developed and other emerging economies. Third, it generates actionable insights for Moroccan regulators, policymakers, and corporate boards seeking to align with international governance standards and post-COVID restructuring imperatives.